Appraisal of gene action for indeterminate growth in mungbean [Vigna radiata (L.) Wilczek] - Iqbal, Javed; Ahsan, Muhammad; Saleem, Muhammad; Ali, Asghar (Frontiers in Plant Science, 2015)
In order to investigate the inheritance pattern of indeterminate growth in Vigna radiata, various related traits were studied. The techniques implied for the purpose were generation mean and variance analyses. Narrow sense heritability estimates were also computed. Four out of fifty greengram accessions were selected during preliminary screen trial based on DDd2 and DDh2 values. Two cross combinations were made with the help of four parents. Generation variance analysis demonstrated the engagement of additive and environmental components, with the pre-pondrance of additive gene action. Narrow sense heritability estimates (>67%) also supported the same. In generation mean analysis both the cross combinations manifested non-allelic epistatic digenic interactions for the investigated traits except for plant height at first flower initiation in both the crosses and for seed yield per plant in one cross, where only additive and dominance components were important. For pyramiding the additive genes which favour determinate plant growth and higher harvest index and simultaneously purging the genes promoting twining growth habit escorted with low seed yield, any modified breeding scheme which could serve the said purpose may be opted.